Алгоритм аналізу системи загроз економічної безпеки бізнес-колаборацій - Чернов, Олександр Олександрович (ФОП Лібуркіна Л. М., 2025)
Метою роботи є побудова алгоритму аналізу системи загроз економічної безпеки бізнес-колаборації, використання якого дозволить підвищити ефективність процесів прийняття і впровадження рішень. Для досягнення зазначеної мети пропонується вирішити такі задачі: визначити систему загроз економічної безпеки бізнес-колаборації, дослідити вертикальні та горизонтальні взаємозв’язки в структурі системи загроз, здійснити упорядкування загроз за ступенем впливу на загальний рівень економічної безпеки бізнес-колаборації. У роботі побудовано трирівневу ієрархію загроз: перший рівень представлено двома класами загроз – зовнішніми та внутрішніми; другий рівень представлено змістовними групами загроз; найнижчий рівень складають безпосередньо загрози. Для проведення аналізу системи загроз пропонується залучити експертні методи оцінювання, а саме метод аналізу ієрархій. У процесі реалізації методу отримано початкові індивідуальні матриці парних порівнянь для груп загроз, на базі яких обчислено відповідні локальні та глобальні пріоритети. В результаті побудовано рейтинг загроз економічної безпеки бізнес-колаборації. До найсуттєвіших загроз із сукупного списку віднесено перші вісім, сукупна частка яких склала понад 50%, і індивідуальні частки перевищують 5%: агресивна цінова політика конкурентів, політична нестабільність, конфлікти інтересів між партнерами, зміни в законодавстві, порушення прав інтелектуальної власності, зміна структури ринку, фінансова нестабільність одного з партнерів. Серед визначених загроз більшість є зовнішніми, і лише дві є внутрішніми (конфлікти інтересів між партнерами та фінансова нестабільність одного з партнерів). Зовнішні загрози представлені двома групами, а саме конкурентними загрозами та загрозами регуляторно-правового середовища. Запропонований алгоритм аналізу системи загроз економічної безпеки бізнес-колаборації дозволяє дослідити зв’язки в структурі системи загроз і здійснити упорядкування загроз за ступенем впливу на загальний рівень економічної безпеки. Використання методу аналізу ієрархій Сааті забезпечує обґрунтовану кількісну оцінку пріоритетів загроз на основі експертних суджень, що підвищує об’єктивність отриманих результатів.

The aim of this work is to develop an algorithm for analyzing the threat system to the economic security of a business collaboration, the use of which will help improve the efficiency of decision-making and implementation processes. To achieve this aim, the following tasks are proposed: identify the threat system to the economic security of a business collaboration, examine vertical and horizontal relationships within the structure of the threat system, and rank threats according to their impact on the overall level of economic security of the business collaboration. The work constructs a three-level threat hierarchy: the first level includes two classes of threats – external and internal; the second level comprises thematic groups of threats; and the lowest level consists of the threats themselves. For analyzing the threat system, it is proposed to use expert evaluation methods, specifically the Analytic Hierarchy Process. During the implementation of the method, initial individual pairwise comparison matrices for threat groups were obtained, based on which the corresponding local and global priorities were calculated. As a result, a ranking of economic security threats to the business collaboration was established. The most significant threats from the overall list include the first eight, whose cumulative share exceeded 50%, and whose individual shares are over 5%: aggressive pricing policy of competitors, political instability, conflicts of interest among partners, changes in legislation, violations of intellectual property rights, changes in market structure, and financial instability of one of the partners. Among the identified threats, most are external, with only two being internal (conflicts of interest among partners and financial instability of one of the partners). External threats are categorized into two groups: competitive threats and threats from the regulatory and legal environment. The proposed algorithm for analyzing the threat system of economic security in a business collaboration allows for the examination of connections within the structure of the threat system and the ranking of threats according to their impact on the overall level of economic security. The use of Saaty’s Analytic Hierarchy Process provides a well-founded quantitative assessment of threat priorities based on expert judgments, which increases the objectivity of the results obtained.
Algorithm for Analyzing the Threat System to the Economic Security of Business Collaborations
Keywords: економічна безпека; загроза; бізнес-коллаборація; ієрархія; система; алгоритм; рейтинг; economic security; threat; business collaboration; hierarchy; system; algorithm; rating